2017
DOI: 10.4103/1735-5362.207199
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compositions and biological activities of Scutellaria pinnatifida A. Hamilt aerial parts

Abstract: Phytochemical analysis of the methanolic and dichloromethane extracts of the aerial parts of Scutellaria pinnatifida led to the isolation of a phenylpropanoid, 1-o-feruloyl-β-D-glucose (1), two known flavonoids including luteolin-7-o-glucoside (2) and apigenin-7-o-glucoside (3), three known phenylethanoid glycosides composed of phlomisethanoside (4), syringalide A (5), and verbascoside (6), and oleic acid (7). Isolation and structural elucidation of compounds were accomplished by HPLC and spectroscopic methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our results match with reported data of Vergun et al [ 31 ], who studied Scutellaria baicalensis in the same fractions and concentrations against DPPH radical. Our study is also in agreement with the study of Grzegorczyk-Karolak et al [ 32 ], Delazar et al [ 33 ] and Zengin et al, [ 34 ] who have performed the same tests for S. altissima and S. pinnatifida , S. Orientalis L . and S. salviifolia .…”
Section: Resultssupporting
confidence: 93%
“…Our results match with reported data of Vergun et al [ 31 ], who studied Scutellaria baicalensis in the same fractions and concentrations against DPPH radical. Our study is also in agreement with the study of Grzegorczyk-Karolak et al [ 32 ], Delazar et al [ 33 ] and Zengin et al, [ 34 ] who have performed the same tests for S. altissima and S. pinnatifida , S. Orientalis L . and S. salviifolia .…”
Section: Resultssupporting
confidence: 93%
“…Roots of Scutellaria baicalensis , S. litwinowii , and S. pinnatifida are used as herbal medicines due to their anti-tumorigenic, anti-fibrotic, anti-inflammatory, and antioxidant effects [2,3,4,5,6,27,28]. Skullcapflavone II is one of the common components of Scutellaria roots, and it is considered a potential therapeutic compound for use in treating cancer, allergic asthma, and bone diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these compositions especially in high value with synergistic effect on cardiac function not only induced no improvement in factors under our investigation, but also developed adverse effects such as arrhythmia. Whereas this plant and other species of this plant contain phenylethanoid and irioid [26][27][28] and cardiac effects of these compounds have already been demonstrated. 7,11,12,28,29 Besides, our previous study showed remarkable cardiovascular effect of S. frigida on isolated rat heart.…”
Section: Discussionmentioning
confidence: 99%